Tele-audiology: Expanding Access to Hearing Care and Enhancing Patient Connectivity. - Gladden, Chad; Beck, Lucille; Chandler, David (Journal of the American Academy of Audiology, 2015)
Background: Tele-audiology within the Department of Veterans Affairs has expanded significantly in response to growing Veteran hearing needs and issues, namely maldistribution of provider resources and continued lags in timely access to care. Although tele-audiology originated from successive telemedicine programs dating back to the early 1960s, the innovation that is currently being developed broadens tele-audiology and hearing care practice to virtual care modalities such as clinical video telehealth, store-and-forward telehealth, home telehealth, mobile health applications, secure messaging, and electronic consults. Purpose: The purpose of this article is to address current and emerging tele-audiology initiatives in context of a connected health care practice model. It includes information on initiatives within the Department of Veterans Affairs, provides an overview of current and potential modalities for improving patient hearing care, and identifies the challenges that exist in implementing and sustaining these services. Information is intended to stimulate creative thinking about future innovative service delivery models. Conclusion: Significant challenges exist in the evolution of innovative tele-audiology services. Despite barriers, these initiatives have the potential to match existing capacity with emerging patient demands in a mutually beneficial partnership and can be successfully integrated into diverse health care and private sector organizations.